Changes in start, end, and length of frost‐free season across Northeast China - Lei Wang; Zhengfang Wu; Hongshi He; Fuxue Wang; Haibo Du; Shengwei Zong (International Journal of Climatology, 2017)
On the basis of the daily minimum temperature, records of 109 meteorological stations over Northeastern China ( NEC ) from 1961 to 2013 and the output data of eight models from CMIP5 , this study investigates the recent and future spatiotemporal changes of the frost‐free season. The results show that the date of last spring frost ( LSFD ) has a significant decreasing trend. Stations exhibiting significant negative trends are mostly distributed in the eastern Jilin Province and the Midwest of Heilongjiang Province. The date of first fall frost ( FFFD ) and length of frost‐free season ( LFFS ) both show significant increasing trends. The spatial patterns of stations showing significant positive trends in the FFFD and LFFS are similar, which are mainly located in the middle part of Eastern Inner Mongolia and the south and middle parts of Changbai Mountains. The LFFSs have significant increasing trends with the magnitudes of 0.49 days/decade for RCP2 .6, 1.62 days/decade for RCP4 .5, and 3.85 days/decade for RCP8 .5 during 2006–2100. The southern Liaoning Province and the northwestern NEC will experience the longer LFFS under each scenario between 2071 and 2100. The frost‐free season indices have significant correlations with the Northern Hemisphere Polar Vortex Area index. The atmospheric circulation patterns of an anticyclonic circulation anomaly prevailed over the Lake Baikal region and a cyclonic circulation anomaly located in the northwest Pacific Ocean in springs and an anticyclonic circulation anomaly prevailed over the south part of the Russian Far East in falls block more cold air flowing into NEC , which result in the earlier LSFD and later FFFD . The adverse patterns in springs and in falls could bring out the later LSFD and earlier LSFD , respectively. Our results could benefit the prevention and reduction of frost disaster and provide a reference for the policy‐making of future crop production.